Protection against allegations of sexual assault when undertaking ultrasound examinations. (February 2017) - Thomson, Nigel; Moloney, Paul
The Medical Defence Union has reported an increase in the numbers of sexual assault allegations against doctors, although these are still thankfully rare. This short article discusses the experience of the Society of Radiographers in advising members who have been accused of sexual assault and identifies ways in which ultrasound practitioners can reduce the risk of having such an accusation made against them.